PM10 emissions from aggregate fractions of an Entic Haplustoll under two contrasting tillage systems - Mendez, Mariano Javier (2015)
Tillage systems affect physical and chemical properties of soils modifying its aggregation. How changes of the aggregate size distribution affect the capacity of the soil to emit fine particulate matter (PM10) to the atmosphere during wind erosion processes, is a less investigated issue. In order to answer this question, PM10 emissions from an Entic Haplustoll submitted to 25 years of continuous conventional tillage (LC) and no-till (NT) were analyzed. Soil samples were sieved with a rotary sieve in order to determine the aggregate size distribution (fractions : <0.42 mm, 0.42–0.84 mm, 0.84–2 mm, 2–6.4 mm, 6.4–19.2 mm, and >19.2 mm), the dry aggregate stability (DAS) and the erodible fraction (EF). The organic matter contents (OM), the particle size composition and the PM10 emission of each aggregate fraction were also measured. Results showed that NT promoted OM accumulations in all aggregate fractions which favored DAS and soil aggregation. The <0.42 mm sized aggregates (27%) predominated in CT and the >19.2 mm (41.7%) in NT, while the proportion of the other aggregate fractions was similar in both tillage systems. As a consequence of the smaller proportion of the <0.42 mm aggregates, the erodible fraction was lower in NT (EF: 17.3%) than in CT (30.8%). PM10 emissions of each aggregate fraction (AE) decreased exponentially with increasing size of the fractions in both tillage systems, mainly as a consequence of the smaller size and higher specific surface. AE was higher in CT than in NT for all aggregate fractions, but the higher differences were found in the <0.42 mm aggregates (18 μg g−1 in CT vs 8 μg g−1 in NT). The PM10 emission of the whole soil was three times higher in CT than in NT, while the emission of the erodible fraction (EFE) was in CT four times higher than in NT. PM10 emissions of the <0.42 mm aggregates represented over 50% of SE and 90% of EFE. We concluded that NT reduced the capacity of soils of the semiarid Pampas to emit PM10 because it produced a better aggregation that reduced the proportion and emission of the <0.42 mm aggregates. These aggregates had, by far, the highest emission potential.